Welfare Effects of Monetary Integration : The Common Monetary Area and Beyond - Asonuma, Tamon (IMF Working Papers; Working Paper ;, 2012)
This paper proposes a quantitative assessment of the welfare effects arising from the Common Monetary Area (CMA) and an array of broader grouping among Southern African Development Community (SADC) countries. Model simulations suggest that (i) participating in the CMA benefits all members; (ii) joining the CMA individually is beneficial for all SADC members except Angola, Mauritius and Tanzania; (iii) creating a symmetric CMA-wide monetary union with a regional central bank carries some costs in terms of foregone anti-inflationary credibility; and (iv) SADC-wide symmetric monetary union continues to be beneficial for all except Mauritius, although the gains for existing CMA members are likely to be limited.